New and future perspectives in Behçet’s syndrome - Bercemhan Sulu; Gulen Hatemi (Archives of Rheumatology, 2024)
Behçet’s syndrome is a variable vessel vasculitis characterized by a diverse range of clinical manifestations resulting from inflammation involving several organs and systems. While significant progress has been made in understanding the pathogenesis and treatment of Behçet’s syndrome, challenges remain in achieving optimal disease control and preventing long-term complications. This review explores recent advances in the management of Behçet’s syndrome, with a focus on emerging therapies and future directions. Apremilast, a phosphodiesterase-4 inhibitor, has shown promise in managing mucocutaneous manifestations, particularly oral ulcers. Tocilizumab, an interleukin (IL)-6 receptor inhibitor, has demonstrated efficacy in certain patient populations, especially those with ocular involvement. However, its use in vascular Behçet’s syndrome requires careful consideration. Relapses of oral and genital ulcers can be challenging during tocilizumab treatment. Other emerging therapies, such as IL-17 inhibitors, including secukinumab and ixekizumab, IL-12/23 inhibitor ustekinumab, and Janus kinase (JAK) inhibitors, including tofacitinib and baricitinib, are being investigated for their potential to target specific inflammatory pathways. Future research directions include the development of novel therapeutic targets, better use of existing agents by identifying patient populations that would benefit from these, developing better instruments for disease assessment, and a treat-to-target approach in order to improve outcomes and quality of life for patients with Behçet’s syndrome.